Neural Processing of Respiratory Sensations when Breathing Becomes More Difficult and Unpleasant - Von Leupoldt, Andreas; Bradley, Margaret M.; Lang, Peter J.; Davenport, Paul W. (Frontiers in Physiology, 2010)
The accurate perception of respiratory sensations is important for the successful management and treatment of respiratory diseases. Previous studies demonstrated that external stimuli such as affective pictures and distracting films can impact the perception and neural processing of respiratory sensations. This study examined the neural processing of respiratory sensations when breathing as an internal stimulus is manipulated and becomes more difficult and unpleasant. Sustained breathing through an inspiratory resistive load was used to increase perceived breathing difficulty in 12 female individuals without respiratory disease. Using high-density EEG, respiratory-related evoked potentials (RREP) to short inspiratory occlusions were recorded at early versus late time points of sustained loaded breathing. Ratings of perceived intensity and unpleasantness of breathing difficulty showed an increase from early to late time points of loaded breathing (p < 0.01 and p < 0.05, respectively). This was paralleled by significant increases in the magnitudes of RREP components N1, P2 and P3 (p < 0.01, p < 0.05 and p < 0.05, respectively). The present results demonstrate increases in the neural processing of respiratory sensations when breathing becomes more difficult and unpleasant. This might reflect a protective neural mechanism allowing effective response behavior when air supply is at risk.